Linking Perfectionism with Moral Behaviors in Sport: The Mediating Role of Burnout and Moral Disengagement - Stanger, Nicholas; Jowett, Gareth E.; Kaiseler, Mariana; Williams, Toni L. (Research quarterly for exercise and sport, 2024)
Purpose: Research has identified a range of intrapersonal variables associated with moral behaviors in sport. However, research investigating how perfectionism and burnout are associated with prosocial and antisocial behavior toward teammates and opponents in sport has received scant attention. In the present study, we address this issue by examining whether perfectionism is associated with prosocial and antisocial behavior in sport directly and indirectly via burnout and moral disengagement. Method: A total of 312 team sport players completed validated measures for each variable. Results: Path analyses revealed that perfectionistic concerns had a negative relationship with prosocial behavior toward teammates and an indirect positive association with antisocial behavior toward both teammates and opponents via being positively associated with burnout, which in turn, was positively associated with moral disengagement. In contrast, perfectionistic strivings had a positive association with prosocial behavior toward teammates, and an indirect positive association with antisocial behavior toward teammates and opponents via moral disengagement. Conclusion: Our findings offer new insights into how perfectionism and burnout are associated with prosocial and antisocial behavior in sport, as well as highlight the need to consider perfectionistic tendencies and approaches to help reduce burnout and moral disengagement in the regulation of antisocial behavior in sport.